Interferon alpha inhibits spinal cord synaptic and nociceptive transmission via neuronal-glial interactions - Liu, Chien-Cheng (Sci Rep, 2016)
It is well known that interferons (IFNs), such as type-I IFN (IFN-α) and type-II IFN (IFN-γ) are produced by immune cells to elicit antiviral effects. IFNs are also produced by glial cells in the CNS to regulate brain functions. As a proinflammatory cytokine, IFN-γ drives neuropathic pain by inducing microglial activation in the spinal cord. However, little is known about the role of IFN-α in regulating pain sensitivity and synaptic transmission. Strikingly, we found that IFN-α/β receptor (type-I IFN receptor) was expressed by primary afferent terminals in the superficial dorsal horn that co-expressed the neuropeptide CGRP. In the spinal cord IFN-α was primarily expressed by astrocytes. Perfusion of spinal cord slices with IFN-α suppressed excitatory synaptic transmission by reducing the frequency of spontaneous excitatory postsynaptic current (sEPSCs). IFN-α also inhibited nociceptive transmission by reducing capsaicin-induced internalization of NK-1 and phosphorylation of extracellular signal-regulated kinase (ERK) in superficial dorsal horn neurons. Finally, spinal (intrathecal) administration of IFN-α reduced inflammatory pain and increased pain threshold in naïve rats, whereas removal of endogenous IFN-α by a neutralizing antibody induced hyperalgesia. Our findings suggest a new form of neuronal-glial interaction by which IFN-α, produced by astrocytes, inhibits nociceptive transmission in the spinal cord.